Tax compliance attitude and behaviour: Gender & ethnicity differences of Malaysian taxpayers - Kasipillai, Jeyapalan (2003)
Prior tax compliance research has focused little on gender as a predictor of compliance.In Malaysia, ethnic background of a taxpayer also could be a major determinant of tax compliance.This study investigates whether gender and ethnicity differences occur in relation to tax compliance attitude and behaviour of Malaysian taxpayers.A personal interview approach is used to obtain information from taxpayers in urban towns. Univariate test suggests that males and females were found to have similar compliant attitudes. As for ethnicity, a similar result was observed.A regression analysis of the data revealed that ethnic factors, academic qualifications and attitude towards noncompliance were statistically significant in relation to income reporting behaviour. The findings of this study are useful for policy implementation in identifying groups that require additional attention to increase voluntary compliance through tax education.